Impact of Low Back Pain Clinical Trials Measured by the Altmetric Score: Cross-Sectional Study - Araujo, Amanda Costa (J Med Internet Res, 2018)
BACKGROUND: There is interest from authors and publishers in sharing the results of their studies over the Internet in order to increase their readership. In this way, articles tend to be discussed and the impact of these articles tends to be increased. In order to measure this type of impact, a new score (named Altmetric) was created. Altmetric aims to understand the individual impact of each article through the attention attracted online. OBJECTIVE: The primary objective of this study was to analyze potential factors related with the publishing journal and the publishing trial that could be associated with Altmetric scores on a random sample of low back pain randomized controlled trials (RCTs). The secondary objective of this study was to describe the characteristics of these trials and their Altmetric scores. METHODS: We searched for all low back pain RCTs indexed on the Physiotherapy Evidence Database (PEDro; www.pedro.org.au) published between 2010 and 2015. A total of 200 articles were randomly selected, and we extracted data related to the publishing trial, the publishing journal, methodological quality of the trials (measured by the 0-10 item PEDro scale), and total and individual scores of Altmetric mentioned and Altmetric reader. The study was a cross-sectional study, and multivariate regression models and descriptive statistics were used. RESULTS: A total of four variables were associated with Altmetric mentioned score: impact factor (β-coefficient=3.4 points), number of years since publication (β-coefficient=–4.9 points), number of citations divided by years since publication (β-coefficient=5.2 points), and descriptive title (β-coefficient=–29.4 points). Only one independent variable was associated with Altmetric reader score: number of citations divided by years since publication (β-coefficient=10.1 points, 95% CI 7.74-12.46). We also found that the majority of articles were published in English, with a descriptive title, and published in open access journals endorsing the Consolidated Standards of Reporting Trials (CONSORT) statement. CONCLUSIONS: Researchers should preferably select high impact factor journals for submission and use declarative or interrogative titles, as these factors are likely to increase the visibility of their studies in social media.